Cytogenetic discrepancy between uncultured amniocytes and cultured amniocytes in mosaic trisomy 15 at amniocentesis - Chih-Ping Chen; Te-Yao Hsu; Tsang-Ming Ko; Schu-Rern Chern; Peih-Shan Wu; Shin-Wen Chen; Fang-Tzu Wu; Yun-Yi Chen; Chen-Chi Lee; Chen-Wen Pan; Wayseen Wang (Elsevier, 2020)
Objective: We present mosaic trisomy 15 at amniocentesis. Materials and methods: A 41-year-old woman underwent amniocentesis at 16 weeks of gestation because of an abnormal non-invasive prenatal testing (NIPT) result suspicious of trisomy 15. Amniocentesis revealed a karyotype of 46,XY. Array comparative genomic hybridization (aCGH) on uncultured amniocytes revealed 26% mosaicism for trisomy 15. She was referred for repeat amniocentesis. aCGH, interphase fluorescence in situ hybridization (FISH), quantitative fluorescent polymerase chain reaction (QF-PCR) assays and/or conventional cytogenetic analysis were applied on various cells and tissues including uncultured amniocytes, cultured amniocytes, cord blood, placenta, parental bloods and/or buccal mucosal cells. Results: Repeat amniocentesis at 21 weeks of gestation revealed a karyotype of 46, XY in cultured amniocytes, and 30% mosaicism for trisomy 15 by aCGH and 32% mosaicism for trisomy 15 by FISH in uncultured amniocytes. Repeat amniocentesis at 29 weeks of gestation revealed a karyotype of 46, XY in cultured amniocytes, and 15% mosaicism for trisomy 15 by aCGH and 7.2% mosaicism for trisomy 15 by FISH in uncultured amniocytes. QF-PCR on cultured amniocytes excluded uniparental disomy (UPD) 15. A phenotypically normal baby was delivered subsequently with a karyotype of 46, XY in cord blood and 2% mosaicism for trisomy 15 by FISH in buccal mucosal cells. The aCGH analysis revealed trisomy 15 in placenta and no genomic imbalance in cord blood. QF-PCR assays determined a maternal origin of trisomy 15 in placenta. Conclusion: Cytogenetic discrepancy may occur between uncultured and cultured amniocytes in mosaic trisomy 15 at amniocentesis. The cells of trisomy 15 cell line in prenatally detected mosaic trisomy 15 may decrease in number as the fetus grows. Whenever NIPT suspects trisomy 15, a confirmatory amniocentesis should include genetic analysis on both uncultured and cultured amniocytes to exclude mosaic trisomy 15 and maternal UPD 15, especially when the cultured amniocytes have a normal karyotype.